Thoughts and emotions evoked by thinking about own death: American versus Japanese undergraduates. - Taku, Kanako; Dominick, Whitney; Jeong, Seokjun; Lee, Raejung; Kim, Jinho (Death Studies, 2026)
The prompts "What emotions does the thought of your own death arouse in you?" and "What will happen to you when your body dies?" have been used to induce anxiety in Terror Management Theory. The current study investigated how the responses to these prompts may reveal cross-national differences by using a text-mining approach. Undergraduates in the US (n = 298) and Japan (n = 212) participated in the study. Across both groups, anxiety was the most common emotion. Cross-national differences also emerged, such that students in the US were more likely to mention sadness, funeral, and religiosity for the first prompt, and acceptance, spiritual change, and religiosity for the second prompt. Students in Japan were more likely to mention regret for the first, and sadness, emptiness, and funeral for the second prompt. Results revealed differences and similarities in thoughts and emotions people associate with when thinking about own death.